Petiveria alliacea L. extract protects against streptozotocin-induced type-2 diabetes by modulating the cAMP/PKA/CREB/cFOS pathway - Oluwafemi Adeleke Ojo; Olufimihan Abolade; Akingbolabo Daniel Ogunlakin; Christopher Oloruntoba Akintayo; Olaoluwa Sesan Olukiran; Olalekan Elijah Odesanmi; Omolola Adenike Ajayi-Odoko; Adebola Busola Ojo; Basiru Olaitan Ajiboye; Samuel Olatunde Dahunsi (Elsevier, 2024)
Objective: This study was designed to investigate the nephroprotective effect and mechanism of action of a methanolic extract of Petiveria alliacea leaves (MEPAL) in streptozotocin-induced diabetic nephropathy (DN) in rats. Methods: Twenty-five Wistar rats were randomly distributed into five groups. Type-2 diabetes was induced by intraperitoneal injection of streptozotocin (40 mg/kg body weight low dose) in citrate buffer (pH 4.5) after administering fructose for two weeks. Diabetic rats with fasting blood glucose above 250 mg/dl were considered diabetic and were divided into: control (distilled water-treated), diabetes-control, diabetes + metformin (100 mg/kg), diabetes + MEPAL (150 mg/kg), and diabetes + MEPAL (300 mg/kg) via oral gavage once daily for 14 days. At the end of the experimental period, the rats were euthanized, and renal tissues were collected for biochemical and histological analyses. Renal apoptosis and marker gene expression were measured by real-time quantitative PCR. Results: MEPAL significantly attenuated diabetic-induced increases in blood glucose levels, kidney body weight, and renal functional indices (ALP, urea, uric acid, and creatinine). MEPAL treatment resulted in a significant reduction in MDA levels and increased activities of SOD, CAT, and GSH levels. In addition, MEPAL protects against DN by significantly downregulating the mRNA expression of cAMP, PKA, CREB, and cFOS and upregulating the Bcl-2 gene, indicating that the nephroprotective effect of MEPAL is due to the modulation of the cAMP/PKA/CREB/cFOS signaling pathways. Furthermore, in the STZ-induced diabetic rats, the kidney tissue showed a thickened basement membrane and degenerated glomerulus while MEPAL and metformin treatment preserved the basement membrane and degenerated glomerulus in treated rats. Conclusion: the findings of this study suggest that MEPAL protects against renal damage in streptozotocin-induced diabetic nephropathic rats.